Ageing Population in Italy: Lessons for Vietnam in policy and implementation - Nguyen, Thuy Ngan (International Journal of Scientific Research and Management (IJSRM), 2025)
Population aging is a pressing global issue, with far-reaching economic and social consequences. A rapidly growing elderly population leads to a shrinking labor force and pressures healthcare and social welfare systems. By 2050, one in six people globally will be over 65 (United Nations). Italy, with over 24% of its population aged 65 and older (ISTAT), is one of the world's oldest countries. Italy has responded with policies including pension reform, employment incentives for older workers, and expanded elderly care.Meanwhile, Vietnam, a developing nation, is rapidly aging, projected to have 18 million people over 65 by 2030 (GSO) with a 2024 fertility rate of only 1.91, below replacement level. This study analyzes Italy’s experience in addressing population aging to draw applicable lessons for Vietnam. Through comparative policy analysis, it identifies key approaches Vietnam could adopt, such as easing healthcare strain, investing in eldercare infrastructure, and promoting extended working life. Findings offer practical implications for future policymaking in aging societies.